1998
DOI: 10.1093/bja/80.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Extradural S(-)-bupivacaine: comparison with racemic RS-bupivacaine

Abstract: Bupivacaine has a chiral centre and is currently available as a racemic mixture of its two enantiomers: R(+)-bupivacaine and S(-)-bupivacaine. Preclinical studies have demonstrated that there is enantiomer selectivity of action with the bulk of central nervous system and cardiovascular toxicity residing with the R(+) isomer. The aim of this study was to compare the clinical efficacy and safety of S(-)-bupivacaine with racemic RS-bupivacaine for extradural anaesthesia. We studied 88 patients undergoing elective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
90
3
9

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(116 citation statements)
references
References 10 publications
13
90
3
9
Order By: Relevance
“…Equipotency between levobupivacaine and the racemate has been recorded by Cox et al who compared 0.75% levobupivacaine, 0.5% levobupivacaine and 0.5% bupivacaine for extradural anaesthesia for lower limb surgery and found no difference in terms of onset times, maximum spread of sensory block or intensity of motor block [20].…”
Section: ¹1mentioning
confidence: 86%
“…Equipotency between levobupivacaine and the racemate has been recorded by Cox et al who compared 0.75% levobupivacaine, 0.5% levobupivacaine and 0.5% bupivacaine for extradural anaesthesia for lower limb surgery and found no difference in terms of onset times, maximum spread of sensory block or intensity of motor block [20].…”
Section: ¹1mentioning
confidence: 86%
“…13 Usage of equal doses of levobupivacaine and bupivacaine were reported in various studies and procedures to provide similar onset of sensory block (8-30 min), maximum cephalic spread (T7-T8) and duration of analgesia (4-6 h). 14,15 Author report the onset of motor block (Bromage scale 1) to be quicker in bupivacaine group than in levobupivacaine group. Kopacz DJ et al also reported the onset of motor block to be delayed with levobupivacaine.…”
Section: Discussionmentioning
confidence: 97%
“…time to start surgery; while others reported no difference between the two groups. [13][14][15] Author report the duration of postoperative analgesia in both bupivacaine and levobupivacaine group to be similar. Casati et al also reported that equipotent dosage of levobupivacaine and bupivacaine provide comparable post-operative pain relief and recovery of sensory and motor function.…”
Section: Discussionmentioning
confidence: 99%
“…9 Owing to the lower affinity of the S (-) isomer to the cardiac sodium channels compared to the R (+) isomer, it is associated with less cardiac side effects. 10,11 Arcioni et al 12 observed that intrathecal and epidural Magnesium Sulphate potentiated and prolonged motor block. They concluded that patients undergoing orthopaedic surgery, supplementation of spinal anaesthesia with combined intrathecal and epidural MgSO4 significantly reduces post-operative analgesic requirements.…”
Section: Discussionmentioning
confidence: 99%